(untitled) - Hejhalova, Bozena (Doprava a spoje, 2011)
As the major problems has been identifined low complexity in provision of transport services by different operation modes and fragmentation of related responsibilities, resulting in poor level in provision of public passenger transport services and decline in share of public passenger transport in the overall number of transported passengers compared to individual car travel. The article proposes possible outcomes in providing transport services within the regions based on integrated transport systems.